(3GdejRGf GdTYQGfjI GdeONdI dLejY CbhGd GdCFeI GdeLJgOjf hebdOje aj GdTQjYI GdeMeOjIs - (3GdnMnfaj GdnqTrYQGfj, CHh eMeO, YHO GdhqgGH Hf CMeO Hf Ydj, J(B973(3g`s ((3eMeO MSfj Hf YHO GdbGOQs)
(3ChdgG (B:s
(3Ydi eG SJhjg GdYde GdEdgj Ke GYde Cf GNJUGU cd WGFaI ef gPg GdCeI HMce ef CMcGe GdTQjYI aj Yde Gddg JYGdis
(3BNQgG (B:s
(3acd Yjf JeSc HgG ChUdJc Edi GdChdi hef TgO gPG GdeTgO aSGhi YfO Gddg LejY GdCbhGd aj GdUMI GfJgis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 180s
(3eYLe GdeDdajf (B2 / 339s
(3cTa GdXfhf (B2 / 1918s
(3TPQGJ GdPgH (B8 / 372s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs